The treaty between the United States and Mexico, the proceedings of the Senate therson, and message of the President and documents communicated therewith : the messages, with correspondence between the executive departament, General Scott and Mr. Trist, and other papers and proceedings of the on Senate in relation thereto, from wich the injuction of secresy has been removed... - Estados Unidos. Tratados, etc (2015)
UANL